Penggunaan Metode Presentasi Untuk Meningatkan Keaktifan Dan Hasil Belajar Siswa Dalam Pembelajaran Pendidikan Pancasila Kelas XI TME 3 - Meda Muhammad Anggulian; Sri Suneki (Departement of Mathematics Education, 2024)
The task of assisting students in their learning is the responsibility of a teacher. Teachers are facilitators in the dynamics of teaching and learning activities. They present materials, handle problems that come up in the classroom, and evaluate student learning outcomes, which cover the stages that come before, during, and after the learning process. The question to be investigated in this study centers on whether using the presentation style can improve learning outcomes and student engagement in the Pancasila Education course. The purpose of this paper is to investigate the possibilities for improving student engagement and learning outcomes through the use of presentational learning strategies. The conclusion that can be drawn from this analysis is that the use of the presentation method is able to improve student learning outcomes in Pancasila Education Lessons